2009
DOI: 10.1128/aem.00226-09
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Endocellular Symbiotic Bacterium of the Macaque Louse Pedicinus obtusus : Distinct Endosymbiont Origins in Anthropoid Primate Lice and the Old World Monkey Louse

Abstract: A symbiotic bacterium of the macaque louse, Pedicinus obtusus, was characterized. The symbiont constituted a gammaproteobacterial lineage distinct from the symbionts of anthropoid primate lice, localized in the midgut epithelium and the ovaries and exhibiting AT-biased genes and accelerated molecular evolution. The designation "Candidatus Puchtella pedicinophila" was proposed for it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…They found that the endosymbiont of Pedicinus obtusus represented a primary endosymbiont independent of C. Riesia , and proposed the name Candidatus Puchtella . Interestingly, phylogenetic reconstruction placed C. Puchtella close to Wigglesworthia , the primary endosymbiont of tsetse flies [35]. Like C. Riesia , C. Puchtella is another louse primary endosymbiont that is closely related to an endosymbiont of a non‐louse blood‐feeding insect.…”
Section: Taxonomy and Phylogeny Of Louse Primary Endosymbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the endosymbiont of Pedicinus obtusus represented a primary endosymbiont independent of C. Riesia , and proposed the name Candidatus Puchtella . Interestingly, phylogenetic reconstruction placed C. Puchtella close to Wigglesworthia , the primary endosymbiont of tsetse flies [35]. Like C. Riesia , C. Puchtella is another louse primary endosymbiont that is closely related to an endosymbiont of a non‐louse blood‐feeding insect.…”
Section: Taxonomy and Phylogeny Of Louse Primary Endosymbiontsmentioning
confidence: 99%
“…A sister clade to the hominid lice is the Pedicinidae, comprising the lice of cercopithecid primates [6]. Fukatsu et al [35] were the first to investigate the phylogenetic placement of primary endosymbionts in the Pedicinidae. They found that the endosymbiont of Pedicinus obtusus represented a primary endosymbiont independent of C. Riesia, and proposed the name Candidatus Puchtella.…”
Section: Taxonomy and Phylogeny Of Louse Primary Endosymbiontsmentioning
confidence: 99%
“…However, the proposed alternatives are long and somewhat awkward Procabacter [83] Procaibacter Based on Appendix 9, the connecting vowel -i-is needed Procabacter acanthamoebae [83] Procaibacter acanthamoebae Based on Appendix 9, the connecting vowel -i-is needed Profftia virida [45] Profftia adelgidis According to Appendix 9, the genitive case of the generic name of the associated organism (Adelges) must be used. Moreover, the epithet virida is malformed Protistobacter heckmanni [84] Protistobacter heckmannii According to Appendix 9, the correct way to form a specific epithet as a genitive noun for a male person whose name ends on -n is to add -ii Puchtella pedicinophila [85] Puchtella pediciniphila Based on Appendix 9, the connecting vowel -i-is needed Rhizobium massiliae [14] Rhizobium massiliense The Latin Massilia with the neuter ending for 'geographical' adjectives -ense gives massiliense Rickettsia amblyommii [86] Rickettsia amblyommatis The genitive of Amblyomma is not amblyommii but (as based on Greek o ' a, genitive o ' ato&) amblyommatis Rickettsia andeanae [87] Rickettsia andeana The authors made an adjective in the genitive case, for which there is no precedent Candidatus name Reference Suggested corrected name Comments in the nomenclature. Possible is andesensis, but the adjective andeanus, -a, -um is widely used Rickettsia asemboensis [88] Rickettsia asembonensis According to Appendix 9, asemboensis must be corrected to asembonensis Rickettsia barbariae [89] Rickettsia barbarica I found no confirmation for the statement by the authors that the name Barbaria was given by the Romans to the mountains of Sardina; it was a general term for the foreign, the uncultivated world.…”
Section: Candidatus Name Reference Suggested Corrected Name Commentsmentioning
confidence: 99%
“…If the most similar sequence from a BLAST search (Altschul et al, 1990) of the non-redundant nucleotide database in GenBank was from an endosymbiont, we identified the sequences as endosymbionts We also downloaded from GenBank 12 endosymbiont sequences from sucking lice and Rhynchophthirina chewing lice (Accessions: DQ076661, DQ076662, DQ076665, DQ076664, EU827263, AB478979, EF110571, EF110573, DQ076667, DQ076666, EF110571, DQ076663; Hypsa & Kirizek 2007;Allen et al, 2009;Fukatsu et al, 2009). Rhynchophthirina is a suborder of blood-feeding chewing lice that is the sister group to Anoplura (Cruickshank et al, 2001;Barker et al, 2003;Johnson, Yoshizawa, & Smith, 2004;Yoshizawa & Johnson, 2010).…”
Section: Louse Endosymbiont Sampling and Sequencingmentioning
confidence: 99%